2017
DOI: 10.1038/s41598-017-12612-z
|View full text |Cite
|
Sign up to set email alerts
|

Designing broad-spectrum anti-HIV-1 gRNAs to target patient-derived variants

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) CRISPR-associated protein 9 (Cas9), including specific guide RNAs (gRNAs), can excise integrated human immunodeficiency virus type 1 (HIV-1) provirus from host chromosomes. To date, anti-HIV-1 gRNAs have been designed to account for off-target activity, however, they seldom account for genetic variation in the HIV-1 genome within and between patients, which will be crucial for therapeutic application of this technology. This analysis tests the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…Pathogens, like the human immunodeficiency virus type 1 (HIV‐1), almost always succeed in causing disease by disabling immune cells, evading the immune system, and acquiring mutations that provide resistance to antiviral drugs. [ 11–14 ] Control of pathogens that have such mechanisms to evade the host immune system necessitates a pharmacological intervention to prevent the disease. Therefore, each pathogen may present a unique set of challenges to the immune system that must be specifically addressed.…”
Section: Infection and Immunitymentioning
confidence: 99%
“…Pathogens, like the human immunodeficiency virus type 1 (HIV‐1), almost always succeed in causing disease by disabling immune cells, evading the immune system, and acquiring mutations that provide resistance to antiviral drugs. [ 11–14 ] Control of pathogens that have such mechanisms to evade the host immune system necessitates a pharmacological intervention to prevent the disease. Therefore, each pathogen may present a unique set of challenges to the immune system that must be specifically addressed.…”
Section: Infection and Immunitymentioning
confidence: 99%
“…Populations of mixed HIV-1 LTR-containing plasmids were subjected to an in vitro cutting assay, as described above, in an effort to explore the most appropriate way of predicting SpCas9 effectiveness against a mixed population of DNA fragments. This mirrors the biological situation found in HIV-1-infected individuals who often contain a swarm of related, yet genetically distinct, integrated viral genomes (Dampier et al, 2017). The script below describes how to compare the predictions of three popular methods with experimentally determined cutting profiles.…”
Section: Taskmentioning
confidence: 82%
“…This will be an invaluable tool for fields editing highly mutable genomes and meta-genomes of mixed populations. In the case of HIV-1, recent research has shown that inter-patient variability presents a barrier to effective targeting (Dampier et al, 2017;Roychoudhury et al, 2018). However, utilizing this tool it was possible to exploit the promiscuity of SpCas9 to construct a set spacers capable of targeting the wide range of known mutations (Dampier et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The integrated HIV-1 copy in this cell line is located in the second intron of SEC16A (chromosome 9, position 136468579), providing a useful cell line for studying HIV-1 latency (3). In order to use J-Lat 10.6 for anti-HIV-1 gene editing and design strategies using the clustered regularly interspaced short palindromic repeats (CRISPR) system, it is necessary to have the full proviral DNA sequence (4)(5)(6)(7)(8)(9)(10)(11). However, the full-length sequence of integrated HIV/R7/E Ϫ /GFP has not been reported.…”
mentioning
confidence: 99%